2019
DOI: 10.1016/j.simpat.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A modular hybrid simulation framework for complex manufacturing system design

Abstract: For complex manufacturing systems, the current hybrid Agent-Based Modelling and Discrete Event Simulation (ABM-DES) frameworks are limited to component and system levels of representation and present a degree of static complexity to study optimal resource planning.To address these limitations, a modular hybrid simulation framework for complex manufacturing system design is presented. A manufacturing system with highly regulated and manual handling processes, composed of multiple repeating modules, is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…However, the existing literature has suggested that hybrid system design and engineering approaches are a suitable approach for the specification and analysis of CPS models due to the limitation of individual methods [45]. In the context of complex manufacturing and supply chain systems, mathematical modelling becomes complicated and computationally expensive due to the complexity and the high level of interactivity of sub-systems [11]. To tackle this challenge, the DES method provides a multi-agent simulation approach for CPS design and is a popular approach to simulate manufacturing processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the existing literature has suggested that hybrid system design and engineering approaches are a suitable approach for the specification and analysis of CPS models due to the limitation of individual methods [45]. In the context of complex manufacturing and supply chain systems, mathematical modelling becomes complicated and computationally expensive due to the complexity and the high level of interactivity of sub-systems [11]. To tackle this challenge, the DES method provides a multi-agent simulation approach for CPS design and is a popular approach to simulate manufacturing processes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the concept of 'agent' has been only used to develop algorithms for individual products' functions with embedded RFID tags [26] and their control systems [5,33]. Complex manufacturing and supply chain systems, consist of several sub-systems (i.e., phases) and sub-sub-systems (i.e., components) that operate simultaneously and interact with each other over time [11]. This paper extends the application of agent-based approach and proposes a multi-agent CPS architecture for complex manufacturing and supply chain systems with embedded RFID technology.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Group dynamics in teams of individuals united by strategic goals are explored in the work (Penagos-Londoño & Ruiz-Moreno, 2019). Farsi et al (2019) use the modular hybrid simulation method to build a model that describes the behavior of complex production systems.…”
Section: Methodsmentioning
confidence: 99%